Mechanism of Replication of Single-Stranded φX174 DNA VII. Circularization of the Progeny Viral Strand - Iwaya, Makoto (1973)
Linear φX174 single-stranded DNA can be isolated from φX phage particles produced under various conditions. About half of the linear strands have a dGMP residue at the 5′ end, the remaining have roughly comparable amounts of dCMP, dTMP, and dAMP. The linear strands can be converted to covalently closed circular molecules by polynucleotide ligase, but only after they have been incubated with T4 DNA polymerase and deoxynucleoside triphosphates. Experiments with endonuclease R, the restriction enzyme from Haemophilus influenzae, indicated that the nucleotides incorporated into the DNA during this reaction were found predominantly in a limited region of the genome. The results suggest that the normal intermediate in single-stranded φX174 DNA synthesis may be a single-stranded linear molecule which is shorter than unit length and is intrinsically capable of circularization.